Biochemical serum profile of quarter mile equines in team penning training - Santos, Roberta de Lima; Rodrigues, Renata Dias; Gomes, Lara Reis; Bizare, Amanda [UNESP]; Oliveira, Wilson Junior; de SOUZA, Rafael Rocha; Gonçalves, Felipe Cesar; Mundim, Antonio Vicente (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2020)
The objective of this work was to evaluate the proteins, minerals, metabolites, and serum enzymes profile in Quarter Mile equines subjected to training for Team Penning competitions by comparing the results before and after training. The animals were from the Agricultural Exhibition Park of Uberlândia (CAMARU), in Uberlândia in the State of Minas Gerais, Brazil. These animals perform constant periodic training with an average duration of two and a half hours per training. Blood samples from twenty male and female equines were collected at the beginning and end of a 45-day interval and then analyzed. A 5 mL blood sample from each animal was collected before and after training by a jugular external venipuncture, and the samples were placed in a tube—without anticoagulant and containing separator gel—to obtain the serum. The components analyzed were: total proteins, albumin, globulins, albumin to globulin ratio (A:G), total and ionized calcium, phosphorus, calcium to phosphorus ratio (Ca:P), cholesterol, triglycerides, creatinine, urea, alkaline phosphatase, ɤ-glutamyl transferase, lactate dehydrogenase (LDH), aspartate amino transferase (AST), alanine aminotransferase (ALT) and creatine kinase (CK). Statistical differences were observed with higher values after exercise for total calcium, ionized calcium, Ca: P ratio, creatinine and ALT and decreased concentrations were found for globulins, phosphorus, cholesterol and triglycerides. Despite the changes observed in the serum concentrations of some elements after exercises, it was concluded that the animals were in adequate physical condition to perform the proposed physical exercises.
Caracterização do perfil bioquímico sérico em equinos quarto de milha submetidos ao treinamento para team penning
Keywords: Horse; Metabolites; Proteins; Serum enzymes; Training